Is maternal depression related to mother and adolescent reports of family functioning?. (February 2018) - Pérez, J. Carola; Coo, Soledad; Irarrázaval, Matías
Abstract: While adolescent-parent disagreements about family functioning are common, they may also be indicative of family members' health problems and may compromise adolescent adjustment. This study examines the association between maternal depressive symptoms and family functioning perceptions, considering both the adolescents' and their mothers' points of view. A sample of 943 Chilean dyads of adolescents (69% female, Mage = 14.43 years old) and their mothers (Mage = 43.20 years) reported their perceptions of family cohesion and adaptability. Mothers also reported their depressive symptoms. Results indicated that mothers perceived their family as more cohesive and more adaptable than their children. There was a negative association between maternal and adolescent reports of family cohesion and maternal depressive symptoms. In the mother' reports, this association depended on adolescent's age. In the case of adolescents' reports, this association depended on adolescent's gender. Finally, maternal depressive symptoms were a significant predictor of mother-adolescent agreement about family cohesion.